Hematological and iron status in aerobic vs. anaerobic female athletes: an observational study - Doaa A. Osman; Mohamed Ismail Elassal; Mohamed Ismail Elassal; Hamada Ahmed Hamada; Reham Hamed Saad Hamza; Hoda Mohammed Zakaria; Reem Alwhaibi; Gehan A. Abdelsamea; Gehan A. Abdelsamea (Frontiers in Sports and Active Living)
IntroductionPhysical training induces iron status impairment in athletic females in the short term and over prolonged periods. Nevertheless, the existing literature lacks a comprehensive evaluation of the differential impacts of aerobic vs. anaerobic training on hematological indices and iron status among adolescent female athletes. The aim of this study was to assess the hematological factors and iron status in aerobic vs. anaerobic training in athletic females.MethodsThis observational, cross-sectional study recruited twenty-five adolescent athletic females; thirteen of them participated in an aerobic sport (long-distance running), while twelve of them participated in an anaerobic sport (broad jumping). Hematological factors were assessed by analyzing blood concentrations of hemoglobin (Hb), hematocrit (Hct), red blood cell (RBC) count, mean corpuscular volume (MCV), and mean corpuscular hemoglobin concentration (MCHC), while the iron status assessment was conducted through evaluating levels of serum transferrin and serum ferritin.ResultsAthletic females who participated in the aerobic sport showed significantly lower Hb (MD −0.84; 95% CI −1.63: −0.04; p = 0.041), Hct (MD −5.49; 95% CI −7.86: −3.12; p = 0.0001), RBC count (MD −0.37; 95% CI −0.57: −0.17; p = 0.001), and MCV (MD −5.15; 95% CI −9.41: −0.89; p = 0.020), as well as significantly higher MCHC (MD 2.99; 95% CI 2.18: 3.79; p = 0.0001) and serum transferrin (MD 46.77; 95% CI 10.95: 82.59; p = 0.013) than athletic females who participated in the anaerobic sport. However, there was an insignificant difference in serum ferritin levels (MD −3.18; 95% CI −11.49: 5.13; p = 0.437) between both groups.ConclusionExcept for the ferritin level that exhibited an insignificant difference between aerobic and anaerobic training, aerobic training was associated with a worse impact on the hematological factors and iron status than anaerobic training in adolescent athletic females.